Porphyromonas gingivalis potentiates stem-like properties of oral squamous cell carcinoma by modulating SCD1-dependent lipid synthesis via NOD1/KLF5 axis - Wenli Zang; Fengxue Geng; Junchao Liu; Zengxu Wang; Shuwei Zhang; Yuchao Li; Ze Lu; Yaping Pan (International Journal of Oral Science)
Abstract Cancer stem cells (CSCs) are widely acknowledged as primary mediators to the initiation and progression of tumors. The association between microbial infection and cancer stemness has garnered considerable scholarly interest in recent years. Porphyromonas gingivalis (P. gingivalis) is increasingly considered to be closely related to the development of oral squamous cell carcinoma (OSCC). Nevertheless, the role of P. gingivalis in the stemness of OSCC cells remains uncertain. Herein, we showed that P. gingivalis was positively correlated with CSC markers expression in human OSCC specimens, promoted the stemness and tumorigenicity of OSCC cells, and enhanced tumor formation in nude mice. Mechanistically, P. gingivalis increased lipid synthesis in OSCC cells by upregulating the expression of stearoyl-CoA desaturase 1 (SCD1) expression, a key enzyme involved in lipid metabolism, which ultimately resulted in enhanced acquisition of stemness. Moreover, SCD1 suppression attenuated P. gingivalis-induced stemness of OSCC cells, including CSCs markers expression, sphere formation ability, chemoresistance, and tumor growth, in OSCC cells both in vitro and in vivo. Additionally, upregulation of SCD1 in P. gingivalis-infected OSCC cells was associated with the expression of KLF5, and that was modulated by P. gingivalis-activated NOD1 signaling. Taken together, these findings highlight the importance of SCD1-dependent lipid synthesis in P. gingivalis-induced stemness acquisition in OSCC cells, suggest that the NOD1/KLF5 axis may play a key role in regulating SCD1 expression and provide a molecular basis for targeting SCD1 as a new option for attenuating OSCC cells stemness.